Analysis Metallothionein of Carp fish in The Brantas River, Indonesia - Putri Ayu Ika Setiyowati; Rofiatun Solekha; Sri Bintang Sahara; Febianti Dwi Hapsari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This study aimed to detection of protein profile, expression of metalothionein (MT) protein, and analyze difference of MT density in liver and gill in one of Carp fish that is Barbonymus balleroides in the upstream and downstream of Brantas river. The method used observasional analytic, Two individual of Barbonymus balleroides samples taken three times (with difference of month) from two station there are upstream and downstream of Brantas river. Analysis protein profile used electrophoresis SDS-PAGE (15%), expression and density of MT used western blot method and imageJ software. Difference between MT density in liver and gill of Barbonymus balleroides in the upstream and downstream of Brantas river analyzed with Two-way ANOVA. The results showed, protein profile in liver and gill Barbonymus balleroides in the upstream and downstream Brantas river have molecular weight about 8-93 kDa, expression of MT showed band of MT with molecular weight 24 kDa, results of MT density in liver and gill on upstream and downstream, continuously 231.29 MT/µm2 and 229.87MT/µm2, 232.41 MT/µm2 and 231.56 MT/µm2 but there is not significant.